2020
DOI: 10.1136/bmjopen-2020-036972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of left bundle branch area pacing versus biventricular pacing in heart failure patients with left bundle branch block: study protocol for a randomised controlled trial

Abstract: IntroductionLeft bundle branch area pacing (LBBaP) has been accepted as a physiological pacing method that can yield narrow paced QRS waves. For patients with failed biventricular pacing (Bi-V), LBBaP is another feasible option. However, no randomised controlled study has evaluated the efficacy and safety of LBBaP in heart failure patients with left bundle branch block (LBBB). Therefore, we aimed to conduct this type of randomised controlled trial.Methods and analysisThis study is a single-centre, randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Firstly, as a meta-analysis of non-randomized controlled studies, although key variables have been frequency-matched, we acknowledged that the potential imbalance of other clinical characteristic of the patients may confound the findings. Ongoing RCTs may validate our findings ( 27 ). Secondly, the number of studies and patients is quite limited, whereas the findings of the studies seemed very consistent.…”
Section: Discussionsupporting
confidence: 69%
“…Firstly, as a meta-analysis of non-randomized controlled studies, although key variables have been frequency-matched, we acknowledged that the potential imbalance of other clinical characteristic of the patients may confound the findings. Ongoing RCTs may validate our findings ( 27 ). Secondly, the number of studies and patients is quite limited, whereas the findings of the studies seemed very consistent.…”
Section: Discussionsupporting
confidence: 69%
“…The LBBP‐RESYNC (Left Bundle Branch Pacing Versus Biventricular Pacing for Cardiac Resynchronization Therapy, NCT04110431) study randomized 40 patients that need CRT in two centers to LBBP or BVP, and the therapeutic effects of LBBP and BVP on LV function and clinical endpoints may recently publish. Additionally, Cheng et al 18 reported a single‐center RCT. This study will consecutively enroll 180 patients with HF and LBBB into LBBP or BVP group (randomized at a 1:1 ratio) from January 2020 to December 2022.…”
Section: Discussionmentioning
confidence: 99%
“…LBBP is an innovation aimed at pacing the LBB conduction system, which could preserve satisfactory LV synchrony and lead to instantly favorable hemodynamic effects 19 . Moreover, LBBP could deliver similar LV electrical and mechanical synchrony compared with either native sinus rhythm or HBP, 18 and most importantly has a better sensing of R‐wave amplitude, a lower and stable pacing threshold and a further but physiological pacing site in case of developing conduction disease. Additionally, LBBP provide more anatomical space for atrioventricular node (AVN) ablation in patients with AF and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Trenutačno je u tijeku prospektivno randomizirano istraživanje u Kini. 49 Nasljedne bolesti srca, procjena rizika, implantabilni kardioverterski defibrilatori i iznenadna smrt…”
Section: Resynchronization Therapy Including His Bundle Septal and Left Bundle Pacingunclassified
“…A prospective randomized study is currently performed in China. 49 inherited cardiac conditions, risk assessment, implantable defibrillators, and sudden death A novel approach to the diagnosis of Brugada syndrome (BrS) described the utilization of autoantibody screening for α-cardiac actin, α-skeletal actin, keratin, and connexin-43. In total, 18/18 BrS subjects demonstrated this autoantibody profile vs. 0/8 normal controls and 0/20 cardiomyopathy cases, which included arrhythmogenic right ventricular cardiomyopathy (ARVC), hypertrophic cardiomyopathy (HCM), and dilated cardiomyopathy (DCM) patients.…”
Section: Resynchronization Therapy Including His Bundle Septal and Left Bundle Pacingmentioning
confidence: 99%